The influence of the specification of climate change damages on the social cost of carbon - Robert E. Kopp; Alexander Golub; Nathaniel O. Keohane; Chikara Onda (Kiel Institute for the World Economy (IfW), 2011)
Drawing upon climate change damage functions previously proposed in the literature that we have calibrated to a common level of damages at 2.5 C, we examine the effect upon the social cost of carbon (SCC) of varying the specification of damages in a DICE-like integrated assessment model. In the absence of risk aversion, all of the SCC estimates but one agree within a factor of two. The effect of varying calibration damages is mildly sublinear. With a moderate level of risk aversion included, however, the differences among estimates grow greatly. By combining elements of different damage specifications and roughly taking into account uncertainty in calibration, we have constructed a composite damage function that attempts to approximate the range of uncertainty in climate change damages. In the absence of risk aversion, SCC values calculated with this function are in agreement with the standard quadratic DICE damage function; with a coefficient of relative risk aversion of 1.4, this damage function yields SCC values more than triple those of the standard function.
Keywords: Q54; Q58; 330; Climate change; social cost of carbon; Kohlendioxid; Klimaveränderung; Soziale Kosten; Umweltbelastung; Klimaschutz; Dynamisches Modell